Leniolisib: a novel treatment for activated phosphoinositide-3 kinase delta syndrome - De, Surya K. (Frontiers in Pharmacology, 2024)
Graphical Abstract IC50 = 11 nM (PI3Kδ); 244 nM (PI3Kα); 424 nM (PI3Kβ), 2,230 nM (PI3Kγ).